2022
DOI: 10.1038/s41467-022-29345-x
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution and surface shock wave of drop impact

Abstract: Drop impact causes severe surface erosion, dictating many important natural, environmental and engineering processes and calling for substantial prevention and preservation efforts. Nevertheless, despite extensive studies on the kinematic features of impacting drops over the last two decades, the dynamic process that leads to the drop-impact erosion is still far from clear. Here, we develop a method of high-speed stress microscopy, which measures the key dynamic properties of drop impact responsible for erosio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…114,115 The rougher surface afforded high WCA although water drops in contact with fabric surfaces shrank over time, indicating that improved hydrophobicity only partially suppressed capillary flow. 116,117 Multiple wetting/dewetting of sample surfaces showed that WCA was stable within 10°of the original value until surface penetration through the cavities. Once penetrated and the cavities wetted, rapid degradation of hydrophobic properties occurs (i.e., WCA ∼30°lower than the original value).…”
Section: ■ Resultsmentioning
confidence: 99%
“…114,115 The rougher surface afforded high WCA although water drops in contact with fabric surfaces shrank over time, indicating that improved hydrophobicity only partially suppressed capillary flow. 116,117 Multiple wetting/dewetting of sample surfaces showed that WCA was stable within 10°of the original value until surface penetration through the cavities. Once penetrated and the cavities wetted, rapid degradation of hydrophobic properties occurs (i.e., WCA ∼30°lower than the original value).…”
Section: ■ Resultsmentioning
confidence: 99%
“…2.1) with Eqs. (2)(3)(4)(5), the characteristic retardation ∆ (i) and azimuth φ (i) at any point in the material are calculated. Then, the final retardation ∆ and azimuth φ are obtained by the Mueller calculus (Eq.…”
Section: Analytical Stress Fieldmentioning
confidence: 99%
“…In this way, it can be used to characterize, for e.g., the level of pain in needle-free drug delivery [1,2]. Additionally, understanding the stress field in the substrate generated during the impact of droplets and liquid jets is related to a wide range of engineering processes and thus is of interest [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of droplets and jets onto other liquids and solid objects is a recurrent phenomenon, both in nature, industrial and medical contexts [1][2][3]. Rain droplets impact bodies of water, leaves or the soil [1,4,5]; droplets for inkjet printing and additive manufacturing impact previously deposited liquid layers or dry paper [6,7]; and in needle-free injections a liquid jet is directed to impact and penetrate the skin [8]. Droplet impacts onto pools have been studied since the works of Arthur Mason Worthington at the start of the 20th century [9].…”
Section: Introductionmentioning
confidence: 99%